PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN DENGAN PERMAINAN HURUF BERLARI PAUD TARAM SPNF SKB TRENGGALEK - Rusmiatin - Rusmiatin (STKIP PGRI TULUNGAGUNG, 2022)
Children aged 3-6 years have a hidden potential to become a good reader. At this age children are easy to recognize letters because it is necessary to choose the right type of game that is suitable for the development of children's learning to read. The ability to read the beginning at PAUD TARAM has not been as successful as expected. Therefore, it is necessary to carry out in order to increase the ability to read the beginning. One way to do this is to use letter running games. This type of research is classroom action research. The research model used is Kemmis and Mc. Taggart using two cycles. Each cycle is carried out in two meetings. The subjects of this study were 19 children. The object of this research is to increase the ability to read the beginning using running letters. Data collection method is done through observation and documentation. The data analysis technique was carried out in a descriptive qualitative and quantitative manner. The results showed that there was an increase in initial reading skills. The increase in the ability to read the beginning can be seen based on the increased percentage of pre-action children who are only 0% m4 has an increase of 21.05% in the first cycle in the second cycle increased 84.21%.